Federal Republic of Yugoslavia : Second Review Under the Stand-By Arrangement and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2002)
This paper highlights the Federal Republic of Yugoslavia's Second Review Under the Stand-By Arrangement and Modification of Performance Criteria. Economic activity is recovering from low levels in the Republic, while progress has been made in lowering inflation. Adjusting for large increases in administered prices and indirect taxes, core inflation is tentatively estimated at about 15-20 percent. The balance of payments feature a widening trade deficit and robust invisible receipts. The authorities are grateful for the wide range of technical assistance they received from the IMF and the World Bank.